Interim measures in international commercial arbitration with seat in Zurich (Switzerland) - Marti, Ulrich (Department of Commercial Law, 2014)
Parties to international commercial transactions choose to refer potential disputes to arbitration instead of litigation for different reasons. In most of the cases an important factor for a decision in favour of arbitration is that they want to have a potential dispute settled quickly. Even if the dispute resolution through arbitration is often speedier than court proceedings, it still takes a fair amount of time until a final award is rendered. Thus, it might become necessary to obtain interim measures to regulate the terms of an ongoing relationship for the duration of the arbitral proceedings, to stabilize matters on a provisional basis or to avoid frustration of the final award. If the need for interim measure arises, the concerned party will be confronted with a bundle of complex legal and tactical questions. The second chapter deals with the question which judicial authority has jurisdiction to order interim measures in international arbitral proceedings conducted in Switzerland, respectively with the legislative and contractual framework that must be considered in order to determine the competent authority. As will be explained, arbitral tribunals and state courts may have concurrent jurisdiction to order interim measures and thus, the parties will have to decide which authority to apply to. To determine which possibility will be more advantageous in the concrete circumstances they have to compare the two options. Thus, the third chapter is concerned with interim measures available to arbitral tribunals, whereas the fourth chapter deals with those available to state courts. In these two chapters the focus is particularly on the variety of interim measures, some procedural aspects and on questions with regard to enforcement. In chapter five some selected questions and problems caused by the concurrent jurisdiction of the arbitral tribunal and the state court will be addressed. I will conclude with the question whether or not one can determine a general rule that it is more advantageous for parties to international arbitration to address either the state court or the arbitral tribunal with a request for interim measure.